(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
"In the article, it is argued that mastering a foreign language enables individuals to keep up with global developments. Simultaneously, it offers a means to disseminate the nation’s culture worldwide. Currently, there is a pressing demand for children to be taught foreign languages seriously, provided that this does not compromise their national identity. In Uzbekistan today, there is considerable discussion about the opportunities available to young people fluent in foreign languages."